2018
DOI: 10.1007/s10120-018-0891-1
|View full text |Cite
|
Sign up to set email alerts
|

Loss of HER2 positivity after anti-HER2 chemotherapy in HER2-positive gastric cancer patients: results of the GASTric cancer HER2 reassessment study 3 (GASTHER3)

Abstract: Background Although discordance in HER2 positivity between primary and metastatic lesions is well established, changes in HER2 positivity after anti-HER2 therapy have not been well evaluated in gastric cancer. We aimed to evaluate whether HER2 expression in gastric cancer is affected by trastuzumab therapy. Methods We enrolled 48 HER2-positive advanced gastric cancer patients treated with trastuzumab-containing first-line chemotherapy and had paired biopsies at baseline and after progression. Results At baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 32 publications
5
67
0
Order By: Relevance
“…Although HER2-targeted therapy has been commonly used in second-line treatment of HER2-positive breast cancer (26), it has failed to be established as second-line treatment in gastric cancer. Consistent with previous studies in gastric cancer (11)(12)(13), we found that two out of three patients with HER2-positive disease treated with trastuzumab in combination with chemotherapy were converted to HER2negative. In addition, our data suggest that cytotoxic chemotherapy can also lead to loss of HER2-positive tumor cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although HER2-targeted therapy has been commonly used in second-line treatment of HER2-positive breast cancer (26), it has failed to be established as second-line treatment in gastric cancer. Consistent with previous studies in gastric cancer (11)(12)(13), we found that two out of three patients with HER2-positive disease treated with trastuzumab in combination with chemotherapy were converted to HER2negative. In addition, our data suggest that cytotoxic chemotherapy can also lead to loss of HER2-positive tumor cells.…”
Section: Discussionsupporting
confidence: 92%
“…One explanation is that HER2 positivity is lost after HER2-targeted treatment. In breast and gastric cancer, it has been reported that previously treated tumors may lose HER2 expression after HER2-targeted therapy (9)(10)(11)(12)(13). The selective pressure of HER2-targeted treatment has been proposed as one of the mechanisms whereby HER2 expression is lost.…”
mentioning
confidence: 99%
“…This could mean HER2 receptor density is lower in GC than BC even in homogenously stained tumors; comparison of HER2 mRNA levels between GC and BC tumors with homogenous HER2 staining does not support this hypothesis (Roche, Data on file); however, more accurate methods to measure exact HER2 receptor density per cell may be needed to test this assumption. Discordance in HER2 expression between primary and metastatic GC has been reported previously, suggesting that HER2 status can be altered or lost during disease progression [36,37]; HER2 status was confirmed using a primary tumor sample for approximately 90% of patients in GATSBY (all had status confirmed using tissue collected prior to first-line therapy). HER2 expression could also have changed before versus after first-line HER2-targeted therapy [38], and in primary versus metastatic tumors during disease progression.…”
Section: Discussionmentioning
confidence: 65%
“…Studies that evaluated changes in HER2 protein expression in AGC patients receiving trastuzumab-containing regimens by comparison of matched pre-and post-treatment samples have demonstrated a loss of HER2 [33,34]. In the aforementioned T-ACT study [21], given that collection of new tumor biopsy samples at the time of study enrollment (after progression on prior trastuzumab therapy) was not mandatory, reassessment of HER2 positivity was performed for only 16 out of 44 patients.…”
Section: Loss Of Her2 Protein Expressionmentioning
confidence: 99%